Regulatory Governance in Brazilian Infrastructure Industries - Correa, Paulo; Melo, Marcus; Mueller, Bernardo; Pereira, Carlos (2012)
The impact of regulation on the economic performance of regulated sectors depends crucially on the appropriateness of the design of the regulatory agencies' structure and process, that is, on regulatory governance. Governance refers not to the policies that emerge from regulation, but rather to the 'inputs' that go into the regulatory process. The current interest in regulatory governance has created the need for a measure to allow comparison among agencies and sectors, as well as over time. Given that there is no obvious way of measuring governance, one solution is to build an index that captures the essence of the concept by translating observable attributes of the regulatory agency and its environment into a number ranging from 0 to 1 (low-to-high quality governance). This paper presents such an index for 21 infrastructure regulatory agencies (federal and state) in Brazil in 2005. This index was based data collected by the authors through questionnaires applied to high-ranking officials at the regulatory agencies. The main index is composed of four sub-indexes that capture issues related to autonomy, decision-making process, tools for effective decision making and accountability. The results show that regulatory governance is relatively similar among the 21 agencies, with better results at the federal than at the state level. In addition it was found that formal attributes do not always translate into effective governance. Of the four dimensions of regulatory governance, the autonomy and accountability were, on average, more developed than decision-making process and regulatory tools.